ANALISIS KUALITAS PRODUK WIRING HARNESS MENGGUNAKAN METODE QUALITY CONTROL CIRCLE (QCC) DAN 5W+1H DI PT EDS MANUFACTURING INDONESIA - gunawan, wawan; Prasetyo, Teguh; Gautama, Pugy (Prodi Teknik Industri, Fakultas Teknik, 2023)
PT EDS Manufacturing Indonesia is dedicated to providing high quality products to its customers. The quality control system implemented ensures that the company does not to: Accept defective products, Manufacture defective products, and Pass defective products. In the January-November 2022 period, there was an increase in defects with an average of 2.2%, which previously in 2021 was only at 1.7%. In order for the products produced to be in accordance with consumer expectations, the company must take effective quality measures made and avoid the large number of damaged or defective products supplied to the market. Quality Control Circle (QCC) is a form of emphasis instrument commonly used in many companies to manage and improve product quality using the PDCA (Plan, Do, Check, Action) cycle. The types of defects that often occur in the production of wirring harness (Suzuki) in the January-November 2022 period are: not click connector defects of 1486, not click docking connector of 726 and missing spot of 473. Known factors that cause the occurrence of not click connectors are: human factors, method factors, and environmental factors. Factors that cause not click docking connectors are: human factors, method factors, and machine factors. The factors causing the missing spot are: human factors and method factors. After the improvement, there was a decrease in the disability rate from the previous condition by an average of 2.2%, to 1.4%. At the stage that has been done, to get sustainable results and continue to control the quality of the products produced, the improvements made need to be made a standard. The standardization is made in the form of SOPs and must be applied to all related elements.